Developments in direct payments - Leece, Janet (Book collections on Project MUSE., 2006)
From a campaigning concept in the 1970s, direct payments - the substitution of cash for services - have become a key part of UK government social care provision. This book charts the change, critically evaluating progress, take-up, inclusion and access to direct payments by different user groups.